Nacionalização das escolas étnicas polonesas do Rio Grande do Sul (1918-1942) - Malikoski, Adriano (My University, 2020)
This research aims to analyze how nacionalização processes, produced in the period from 1918 to 1942, configured or extinguished the ethnic schools of Polish communities in Rio Grande do Sul, observing the reactions and actions of different institutions in their ethnic identity process, present in this historical context of imposing construction of a nationality model. The problem comes down to understanding how the school process of Polish immigrants was configured and organized, from the reconstruction of Poland on the political map of Europe, in the face of the nationalist cultural imposition, better known as the Campanha de Nacionalização, with restrictions on ethnic school organizations. Through the theoretical assumptions of Cultural History, by authors such as Chartier (1988) and Certeau (2011) and Barth's (1998) understanding of ethnicity, I consider it important to pay attention to the ethnic school processes experienced in the context, after the implementation of the Estado Novo in 1937 and how such practices were perceived and felt. Methodologically, I understand the construction of historiography as a systematic organization of sources, according to the questions and research objectives, in a limited time and space. Among the different documents mobilized for the construction of this thesis, are consular documents; correspondence from Polish societies and ethnic organizations; articles from the ethnic press, as well as images and school documents of Polish immigrants. I argue that the affirmation of Brazilianness in the Era Vargas and the constitution of a Polishness, influenced by the Polish Ministry of Foreign Affairs, were important elements to configure teaching activities, during the interwar period, resulting in the extinction or transformation of ethnic schools in these communities in Rio Grande do Sul. It was a non-homogeneous process of redefinition of ethnic culture and the constitution of the symbolic, in its sense of value and in a dimension of production of belongings, here, in particular, of Polish immigrants. In this environment, there was an increase in the relations between the construction of Polishness and the constitution and conduct of school processes, included in a political order, through the monitoring of the Polish government. The construction and maintenance of cultural practices by Polish immigrants enabled the formation of several institutions even before Poland's independence, such as associations, societies and schools. For Poles, the ethnic school process was a marker of Polishness, synonymous with resistance to theinstitutionalized processes of nationalization, coupled with the feeling of belonging, which contributed to the ethnic culture being formulated and constituted in a certain way. As a result of the Vargas nationalization campaign, the ethnic school education of Polish immigrants was stopped by the moral imposition of an ideal of Brazilianness that resulted in the transformation and closure of schools and restrictions on the use of ethnic culture.
Esta pesquisa tem por objetivo analisar como processos de nacionalização, produzidos no período de 1918 a 1942, configuraram ou extinguiram as escolas étnicas de comunidades polonesas no Rio Grande do Sul, observando as reações e as ações de diferentes instituições no seu processo identitário étnico, presentes neste contexto histórico de construção impositiva de um modelo de nacionalidade. A problemática se resume em compreender como foi configurado e organizado o processo escolar dos imigrantes poloneses, a partir da reconstrução da Polônia no mapa político da Europa, diante da imposição cultural nacionalista, mais conhecida como Campanha de Nacionalização, com restrições às organizações escolares étnicas. Por meio dos pressupostos teóricos da História Cultural, de autores como Chartier (1988) e Certeau (2011) e do entendimento de etnicidade de Barth (1998), considero importante atentar para os processos escolares étnicos vividos no contexto gaúcho, após a implementação do Estado Novo em 1937 e como tais práticas foram percebidas e sentidas. Metodologicamente compreendo a construção da historiografia como uma organização sistemática de fontes, conforme os questionamentos e objetivos de pesquisa, em tempo e espaço delimitado. Dentre os diferentes documentos mobilizados para a construção desta tese, estão documentos consulares; correspondências de sociedades e organizações étnicas polonesas; artigos da imprensa étnica, além de imagens e documentos escolares de imigrantes poloneses. Defendo que a afirmação de brasilidade na Era Vargas e a constituição de uma polonidade, influenciada pelo Ministério das Relações Exteriores da Polônia, foram elementos importantes para configurar as atividades de ensino, durante o período entreguerras, resultando na extinção ou transformação das escolas étnicas nessas comunidades no Rio Grande do Sul. Foi um processo não homogêneo de ressignificação da cultura étnica e da constituição do simbólico, em sua acepção de valor e numa dimensão de produção de pertencimentos, aqui, em especial, dos imigrantes poloneses. Neste ambiente houve incremento nas relações entre a construção de polonidade e a constituição e condução dos processos escolares, incluídos numa ordem política, por meio do acompanhamento do governo da Polônia. A construção e a manutenção de práticas culturais dos imigrantes poloneses possibilitaram a formação de diversas instituições ainda anteriores à independência da Polônia, como associações, sociedades e escolas. Para os poloneses o processo escolar étnico foi um demarcador de polonidade, sinônimo de resistência frente aos processos institucionalizados da nacionalização, aliados ao sentimento de pertencimento, que contribuiu para que a cultura étnica fosse formulada e constituída de certo modo. Como resultado da campanha de nacionalização varguista, o ensino escolar étnico dos imigrantes poloneses foi cessado pela imposição moral de um ideal de brasilidade que resultou na transformação e no fechamento de escolas e em restrições de utilização da cultura étnica.
Keywords: Poloneses - Rio Grande do Sul - História; Poloneses - Rio Grande do Sul - Educação; Nacionalização; Imigrantes - Rio Grande do Sul - História; Polônia - Migração; Poles - Rio Grande do Sul - History; Poles - Rio Grande do Sul - Education; Nationalization; Immigrants - Rio Grande do Sul - History; Poland - Migration